(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Ayurveda is an ancient science and it has a Holistic approach. There are eight branches of Ayurveda mentioned in “Ashtang Ayurved”. One of them being Vrush-Chikitsa (Vajikarana Tantra). The branch deals with Alpa Shukra, Kshina Shukra, Vishushka Retasa, Utpatti, Pushthi and Vruddhi of Shukra Dhatu which can be correlated with modern terminologies such as Oligospermia, Asthenozoospermia, Teratozoospermia, Hypospermia (all are indicative of Defective Seminal parameters) along with ejaculatory defects and helps in spermatogenesis. Thus ‘Vrushya’ indicates the substance by virtue of which a person is capable to act sexually like ‘Vrisha’ (bull). Vrushya has been described as ‘Shukrajanaka’ which can be correlated to spermatogenesis. Whereas, Vajikarana is mentioned as ‘Shukra Pravartanam’ which can be defined as ejaculation which helps in the release of semen from the body. There are many Ayurvedic herbs which have the property of ‘Vrushya’. Infertility is a serious health issue worldwide, affecting approximately 8 -10% of couples worldwide. 40-50% is due to “Male factor” infertility and as many as 2% of all men will exhibit suboptimal sperm parameters. The problem of infertility exists in this day and age and one of the most prominent things of Ayurveda is that a separate branch has been mentioned in “Ashtang Ayurved”, so it is of utmost importance for us as practitioners to find the medicinal plants acting on Shukra Dhatu to tackle this problem. The attempt of this study is to highlight the plants mentioned as Vrushya in Bhavprakash Nighantu